AN ANALYSIS OF POST-TRAUMATIC STRESS DISORDER (PTSD) REFLECTED IN THE MAIN CHARACTER OF JEFFREY DAHMER IN â€œMONSTER: JEFFREY DAHMER STORYâ€ (2022) - Via Ifani; Puji Laksono (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2023)
This study is aimed to analyze the psychological condition of Dahmer as Post-Traumatic Stress disorderâ€™s sufferer reflected in â€œMonster: Jeffrey Dahmer Storyâ€ and the negative Impact of Post-Traumatic Stress Disorder (PTSD) reflected in the main character. The study uses descriptive qualitative. The collecting data of the research method includes watching and reading, identifying, classifying, and selecting. The analyzing data of the research method by used displaying, explaining, and interpreting. The researcher analyzes the data by using Post-Traumatic Stress Disorder and Sigmund Freud Psychoanalysis. The result of the study: (1) the causes of Post-Traumatic Stress Disorder (PTSD) reflected in the main character of Jeffrey Dahmer in â€œMonster: Jeffrey Dahmer Storyâ€ such as Physical, Sexual and Emotional Abuse, Violence in Children and Teens and Child Sexual Abuse; (2) the psychological condition of Jeffrey Dahmer as Post-Traumatic Stress Disorder sufferer in form of Negative Reaction, Hyper Arousal Exposure to Stressor and re-experience event by using Sigmund Freud Psychoanalysis.(3) the negative impact of Post-Traumatic Stress Disorder (PTSD) of Jeffrey Dahmer such as being a psychopath, cannibalism, mutilation and sexual abnormalities.